Susceptibility to chronic social stress increases plaque progression, vulnerability and platelet activation - Giannarelli, Chiara; Rodriguez, David T.; Urooj Zafar, M.; Christoffel, Daniel; Vialou, Vincent; Peña, Catherine; Badimon, Ana; Hodes, Georgia F.; Mury, Pauline; Rabkin, Jacklyn; Alique, Matilde; Villa, Giulia; Argmann, Carmen; Nestler, Eric J.; Russo, Scott J.; Badimon, Juan J. (Thrombosis and Haemostasis, 2017)
Supplementary Material to this article is available online at www.thrombosis-online.com.